Swiss Suggestions For A Multidisciplinary Approach To Treating Sudden Cardiac Death In Forensic Medicine (International Journal of Food and Nutritional Sciences, 2022)
Sudden cardiac death (SCD) is a cardiac condition that is by definition unexpected. A forensic pathologist usually always conducts the inquiry. In these situations, the forensic pathologist has two roles:(1) to quickly and accurately ascertain the cause and manner of death, and (2) to launch a multidisciplinary approach to stop additional deaths among current family members. The district attorney in charge frequently declines additional investigations if it is determined that the death was brought on by ‘natural’ reasons. To determine the exact cause of death, additional tests, such as in-depth histopathological investigations and/or molecular genetic analysis, are frequently required. In an effort to unify the methodology used to study SCD, the Swiss Society of Legal Medicine established a multidisciplinary working group involving clinical and molecular geneticists and cardiologists. In to enhance the diagnostic processes and preventive measures for family members who are still alive, the goal of this paper is to bridge the gap between the clinical recommendations for genetic testing of inherited cardiac diseases and the Swiss recommendations for routine forensic postmortem cardiac examinationThe main recommendations are as follows: 1. do forensic autopsies on all SCD victims under the age of 40; 2. gather and store sufficient samples for genetic testing; 3. communicate with the families; and 4. adopt a multidisciplinary strategy incorporating cardiogenetic counselling.